KIPRAH KOPERASI SYARIAH DALAM MENGELOLA PASAR TRADISIONAL MENURUT PERATURAN MENTERI KOPERASI DAN USAHA KECIL DAN MENENGAH NOMOR : 11/PER/M.KUKM/XII/2017 - ISMAK SUBARDAN; I MADE SURADANA; TRI LAKSONO KURNIAWAN; BAIQ NURAINI DWI S (Universitas Mahasaraswati K. Mataram, 2021)
Today's sharia cooperatives have begun to show a very positive view among the community, where the mindset is built that by adhering to sharia principles there will be no element of usury in running their business so that people feel safer if they join cooperatives. Traditional market management by sharia cooperatives will be much more useful and make it easier for members to obtain business capital loans in the form of sharia concepts. With the issuance of this cooperative ministerial regulation which will regulate savings and loan business activities and sharia financing, it will foster the passion of traditional markets because market traders will be helped directly from the financing aspect in carrying out their business activities. Sharia savings and loan and financing activities by sharia cooperatives will encourage the openness of the mental attitude of traders who feel protected from usury behavior and will get blessings for any business profits obtained, if this is embedded in the mindset of every market trader then it is only natural that the market will advance and the community will be spared from business patterns that contain usury element. Traditional markets under the management of sharia cooperatives sooner or later the community paradigm will wake up that traditional market activities will change the designation to the term sharia market. The regulation of the minister of cooperatives and small and medium enterprises number: 11/Per/M.KUKM/XII/2017 concerning the implementation of savings and loan business activities and sharia financing by cooperatives has provided a very significant space for traditional market traders in running their business.